Treatment of Tissue Thromboplastin Membranes with Phospholipase C - Bjørklid, E; Otnæss, A.-B; Storm, E; Prydz, H; Johansen, B. V; Frøholm, L. O (Thrombosis and Haemostasis, 1973)
Tissue thromboplastin from human brain, partially purified by extraction with deoxycholate, gel chromatography and recombination of the protein (fraction A) and phospholipid (fraction B) fractions, was examined after treatment with phospholipase C (E.C. 3.1.4.3). Various morphological changes accompanied the loss in coagulation activity caused by the enzyme. All concentrically arranged vesicles (spherulites) disappeared. Instead, a large number of quite small vesicles and many big “blebs”, probably containing diglycerides, were seen. Fused membranes appeared after treatment with the enzyme. The phospholipid fraction (fraction B) showed similar structures as thromboplastin, but not quite the same morphological changes after enzyme treatment.Phospholipase C treatment probably caused a splitting of the concentrically arranged tissue thromboplastin membranes, which spontaneously rearranged to form new vesicles or were fused to other membranes. The hydrophilic parts of the phospholipids are required for coagulation activity, either because they impart a certain ultrastructure to the membrane, or because they participate in the coagulation process in a more direct way, e.g. by forming complexes with factor VII or by binding factor VII through calcium bridges.